2016
DOI: 10.1063/1.4962389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tomography resolution on the calculated microscopic properties of porous materials: Comparison of sandstone and carbonate rocks

Abstract: Effect of tomography resolution on the calculated microscopic properties of porous materials: comparison of sandstone and carbonate rocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…However, it has been shown that the spatial resolution of the 3D reconstruction has to be much finer than the morphological feature size to ensure that possible effects of medium structure on the transport characteristics are adequately captured. 37 Only in a few studies, information on the void space, obtained by physical reconstruction of porous materials with sufficiently fine resolution, was used to investigate numerically the diffusion of finite-size tracer particles. Langford et al 15 employed Brownian dynamics simulations to model diffusion of spherical probes of different sizes (varying from 0 up to 70 nm) in chromatographic adsorbents physically reconstructed using electron tomography with a resolution of about 3 × 3 × 5 nm.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, it has been shown that the spatial resolution of the 3D reconstruction has to be much finer than the morphological feature size to ensure that possible effects of medium structure on the transport characteristics are adequately captured. 37 Only in a few studies, information on the void space, obtained by physical reconstruction of porous materials with sufficiently fine resolution, was used to investigate numerically the diffusion of finite-size tracer particles. Langford et al 15 employed Brownian dynamics simulations to model diffusion of spherical probes of different sizes (varying from 0 up to 70 nm) in chromatographic adsorbents physically reconstructed using electron tomography with a resolution of about 3 × 3 × 5 nm.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This indicated that the sample was quite homogeneous and that the sampling volume we selected was a good representation of the material. The pore analysis of the sample 32 indicated that the pore radii within the volume ranged between 0.2 μ m and 1.0 μ m and the average pore radius was 0.4 μ m. The calculated absolute permeability for the volume, determined using the method described by Gooya et al . 32 , was 9.06 mD, which is within the range expected for chalk 33 .…”
Section: Resultsmentioning
confidence: 99%
“…The pore analysis of the sample 32 indicated that the pore radii within the volume ranged between 0.2 μ m and 1.0 μ m and the average pore radius was 0.4 μ m. The calculated absolute permeability for the volume, determined using the method described by Gooya et al . 32 , was 9.06 mD, which is within the range expected for chalk 33 . Because of the sample’s demonstrated homogeneity and because of computational limitations, we chose to use a 100 3 voxel volume, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously analysed the effect of imaging resolution in two numerical contexts. We used a conventional CFD approach (finite volume method to solve the Stokes equation on binarised tomogram [ 48 ]) to show that the influence is rock type specific and is predominately reflected in the interconnectivity of pore spaces that require discretisation. We have also applied the reactor network model on tomographic data at three different resolutions [ 34 ].…”
Section: Discussionmentioning
confidence: 99%